Mycoplasma genitalium, Chlamydia trachomatis, and Neisseria gonorrhoeae Detected With Aptima Assays Performed on Self-Obtained Vaginal Swabs and Urine Collected at Home and in a Clinic. Issue 9 (September 2019) - Chernesky, Max; Jang, Dan; Martin, Irene; Arias, Manuel; Shah, Anika; Smieja, Marek; Ratnam, Sam; Getman, Damon; Schachter, Julius
Abstract : Abstract: Self-obtained vaginal swabs, first-void urine and pooled specimens were collected at home and in a clinic. Percent prevalence and collection site concordance was 30.3 and 100 for Mycoplasma genitalium (74.4% azithromycin resistant) 15.1 and 96.7 for Chlamydia trachomatis and 6.6 and 100 for Neisseria gonorrhoeae (27% ciprofloxacin-resistant). Abstract : Female self-obtained specimens collected and pooled at home and in clinic showed similar detection rates in each setting for Mycoplasma genitalium, Chlamydia trachomatis, and Neisseria gonorrhoeae. Antimicrobial resistance was determined.